2002
DOI: 10.1124/dmd.30.12.1344
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CYP3A in the Metabolism of Eplerenone in Humans and Dogs: Differential Metabolism by CYP3A4 and CYP3A5

Abstract: ABSTRACT:In vitro studies were conducted to identify the major metabolites of eplerenone (EP) and the cytochrome P450 (P450) isozymes involved in its primary oxidative metabolism in humans and dogs. The major in vitro metabolites were identified as 6␤-hydroxy EP and 21-hydroxy EP in both humans and dogs. EP was metabolized by cDNA-expressed human CYP3A4 and dog CYP3A12 but only minimally by human CYP3A5. In human microsomes, inhibition of total metabolism by the CYP3A-selective inhibitors ketoconazole, trolean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 17 publications
(16 reference statements)
0
27
0
5
Order By: Relevance
“…The primary route of elimination for eplerenone is through CYP 450 3A4-mediated metabolism [20]. The apparent plasma clearance of eplerenone is ≈10L/hr and its elimination half-life is 4 to 6-hrs.…”
Section: Eplerenonementioning
confidence: 99%
“…The primary route of elimination for eplerenone is through CYP 450 3A4-mediated metabolism [20]. The apparent plasma clearance of eplerenone is ≈10L/hr and its elimination half-life is 4 to 6-hrs.…”
Section: Eplerenonementioning
confidence: 99%
“…Recently, however, CYP3A5 is reported to be more abundant than CYP3A4 in the lung and kidney (Ding and Kaminsky, 2003). CYP3A4-specific probe substrates and/or inactivators have been identified (Cook et al, 2002;Khan et al, 2002), but specific probe substrates for CYP3A5 have not yet been reported. CYP3A7 is the major fetal form and is rarely expressed in adults.…”
Section: Introductionmentioning
confidence: 99%
“…There are 84% amino acid sequence similarity and overlapping substrate specificities between CYP3A4 and CYP3A5 (Aoyama et al, 1989;Wrighton and Stevens, 1992). However, some differences have been reported in enzymatic properties of CYP3A4 and CYP3A5, including substrate specificity and inhibition (Gibbs et al, 1999;Cook et al, 2002;Patki et al, 2003;Emoto and Iwasaki, 2006). Unlike CYP3A4, CYP3A5 is polymorphically expressed in human liver (Koch et al, 2002;Xie et al, 2004).…”
Section: Introductionmentioning
confidence: 99%